2015
DOI: 10.1590/1982-0224-20140083
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive studies of Anchoa marinii Hildebrand, 1943 (Actinopterygii: Engraulidae) in the nearby-coastal area of Mar Chiquita coastal lagoon, Buenos Aires, Argentina

Abstract: The aim of the present study provides the first results on the reproductive biology of the anchovy, Anchoa marinii, in a nearby-coastal area of Mar Chiquita coastal lagoon, 37º32'00"S 57º19'00"W, Argentina. To perform this, we employed mainly female gonads, at both microscopic and macroscopic levels. The oocyte diameter distribution and the microscopy analysis of oocytes, showed different batches of growing oocytes, suggesting that the anchovy is a multiple spawner, with constant oocytes recruitment all over t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Also, no significant correlation was found between the fecundity and the variables "weight" and "length". This fact was reported by Macchi & Acha (2000) for this species, but also for other species of Clupeiformes with similar reproductive strategies (López et al, 2013). The females used in this work correspond to the asymptote of infinity length, of the growth curve of Lopez-Cazorla (1985).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Also, no significant correlation was found between the fecundity and the variables "weight" and "length". This fact was reported by Macchi & Acha (2000) for this species, but also for other species of Clupeiformes with similar reproductive strategies (López et al, 2013). The females used in this work correspond to the asymptote of infinity length, of the growth curve of Lopez-Cazorla (1985).…”
Section: Discussionsupporting
confidence: 79%
“…These values are much greater than those of the most important local species of Clupeiformes with similar reproductive strategies. For example, batch fecundity estimated of Anchoa marinii was 749 to 3,207 oocytes, (López et al, 2013). Rodrigues et al (2008) reported a batch fecundity of 570-2,026 oocytes for Ramnogaster arcuata specimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of A. marinii is closely associated with the cold waters transported by the Brazilian Coastal Current, similar to other engraulid species in the area (Franco et al, 2006). Based on the reconstructed length of fish consumed by SAFSs, it was observed that the majority of A. marinii individuals were mature (López et al, 2015).…”
Section: Discussionmentioning
confidence: 99%